2007
DOI: 10.1080/15476910601115184
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Ethanolic Extract of Seeds ofMoringa oleiferaLam. Against Inflammation Associated with Development of Arthritis in Rats

Abstract: The present investigation was carried out to study the anti-arthritic activity of ethanolic extract of seeds of Moringa oleifera Lam. (MOEE) in adjuvant-induced arthritis in adult female Wistar rats. During the experimental period, body weight, paw edema volume (primary lesion) and arthritic index (secondary lesion) was observed. On the 21st day, serum from each animal was used for estimation of Rheumatoid Factor (RF) value and levels of selected cytokines (TNFalpha, IL-1, and IL-6). Whole blood was used for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
43
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(51 citation statements)
references
References 53 publications
6
43
0
1
Order By: Relevance
“…The assessed inflammatory biomarkers, ESR and TNF-α, showed extreme elevation in the control adjuvant arthritic rats compared to the normal control. This result was in agreement with the work of Glenn & Kooyers (1966) and Mahajan et al (2007).…”
Section: Discussionsupporting
confidence: 93%
“…The assessed inflammatory biomarkers, ESR and TNF-α, showed extreme elevation in the control adjuvant arthritic rats compared to the normal control. This result was in agreement with the work of Glenn & Kooyers (1966) and Mahajan et al (2007).…”
Section: Discussionsupporting
confidence: 93%
“…TNF-α was the biomarker of inflammation assessed in the present study and showed extreme elevation in the control adjuvant arthritic rats compared to the normal control. This result was in agreement with the work of Glenn & Kooyers (1966) and Mahajan et al (2007). The elevation in the plasma levels of MDA in the arthritic control rats in the current research is in In each column the same letter means non significant difference, while different letters mean significant difference at 0.05 probability.…”
Section: Discussionsupporting
confidence: 93%
“…Our study agrees with Mahmoud [57]. The hepatoprotective effect of Moringa oleifera against liver inflammation is attained by its reduction of the liver content of TNF-α and this was agreed with Mahajan et al [58]. The same action also happened with administration of silymarin that decreased TNF-α liver content, these results agree with Song et al [59].…”
Section: Discussionsupporting
confidence: 92%